2013
DOI: 10.1186/1756-0500-6-106
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and utilization of computer among health workers in Addis Ababa hospitals, Ethiopia: computer literacy in the health sector

Abstract: BackgroundIncorporation of information technology advancements in healthcare has gained wide acceptance in the last two decades. Developed countries have successfully incorporated information technology advancements in their healthcare system thus, improving healthcare. However, only a limited application of information technology advancements is seen in developing countries in their healthcare system. Hence, this study was aimed at assessing knowledge and utilization of computer among health workers in Addis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
30
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 6 publications
8
30
6
1
Order By: Relevance
“…This might be due to the fact that most Nigerian women who are mothers after office work engage in domestic activities, thereby having little or no time for computer practice unlike their male counterpart. Another reason could be that fewer females possess personal computers and this corroborates the findings of [2].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…This might be due to the fact that most Nigerian women who are mothers after office work engage in domestic activities, thereby having little or no time for computer practice unlike their male counterpart. Another reason could be that fewer females possess personal computers and this corroborates the findings of [2].…”
Section: Discussionsupporting
confidence: 67%
“…Other authors [2,14] in their respective studies had earlier revealed similar low patterns. In contrast, studies [15,16] in different places reported higher patterns from their research.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Developed countries have successfully adapted it within healthcare organizations. Compared to developed, countries developing countries have limited application of it in thier healthcare institutions (Mohammed, Andargie, Meseret & Girma, 2013). Furthermore, Jeon et al (2016) concluded that informatics in nursing education have increased during the last decade.…”
mentioning
confidence: 99%